Regulating Crime and the International Crime Drop - Clarke, Ronald (International criminal justice review, 2021)
Michael Quinn’s article reveals that Jeremy Bentham strongly endorsed the suggestions of Patrick Colquhoun, a London magistrate, for reducing the myriad of tempting opportunities for crime in large cities like London. However, it was Colquhoun’s other, positivist ideas about training the poor to resist these temptations that helped determine crime policy for the next 150 years. This positivist agenda has recently been criticized by environmental criminologists and crime scientists, who have revived Colquhoun’s ideas about reducing opportunities for crime and who have advanced the security hypothesis as the explanation for the international drop in crime.